2019
DOI: 10.2169/internalmedicine.1918-18
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Nodular Pulmonary Aspergillosis in a Patient with Rheumatoid Arthritis

Abstract: Chronic pulmonary aspergillosis, which features nodular lesions known as Aspergillus nodules, is a relatively uncommon disorder. We herein report a case of slowly progressing chronic multiple nodular pulmonary aspergillosis in a 59-year-old man with rheumatoid arthritis, dyspnea, and fatigue. One nodule was surgically resected. The surgical specimen featured central necrosis and was located adjacent to a respiratory bronchiole and pulmonary artery, without parenchymal invasion. Branching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…In addition, 90% (18/20) of the Aspergillus nodules for which data were available showed high SUV max uptake on FDG-PET/CT. As malignant nodules or granulomatous nodules, due to tuberculosis or nontuberculous mycobacteria, can show positive signals on PET [25], our data suggested that radiological imaging alone is unlikely to be useful for the differentiation of Aspergillus nodules from other etiologies [26]. Thorough investigations, including preoperative histological confirmation, should be considered before undertaking surgical resection to avoid unnecessary intervention or the misdiagnosis of benign conditions [9,26].…”
Section: Discussionmentioning
confidence: 91%
“…In addition, 90% (18/20) of the Aspergillus nodules for which data were available showed high SUV max uptake on FDG-PET/CT. As malignant nodules or granulomatous nodules, due to tuberculosis or nontuberculous mycobacteria, can show positive signals on PET [25], our data suggested that radiological imaging alone is unlikely to be useful for the differentiation of Aspergillus nodules from other etiologies [26]. Thorough investigations, including preoperative histological confirmation, should be considered before undertaking surgical resection to avoid unnecessary intervention or the misdiagnosis of benign conditions [9,26].…”
Section: Discussionmentioning
confidence: 91%
“…Aspergillus nodules have been defined as one or more small nodules in the lungs (<3 mm in diameter), which may or may not cavitate. 12,24 Some authors have also included lesions that are slightly larger into the definition, 28,40 whereas others differentiate nodules bigger than 3 mm in size, with necrotic centers, as being Aspergillus mass lesions. 32 Macroscopically, Aspergillus nodules might be either smooth or lobulated, are sometimes calcified and may occasionally be associated with enlargement of the regional lymph nodes.…”
Section: Aspergillus Nodulesmentioning
confidence: 99%
“…12,26,28 Due to this indistinguishabi-lity from other diseases, a definitive diagnosis is based on histological examination of biopsies and bronchoalveolar lavage fluid. 24,26 Histopathological manifestations of Aspergillus nodules include hyphal growth within granulomas/ pyogranulomas, with surrounding dense fibrous capsules 25,40,42 (►Fig. 7).…”
Section: Aspergillus Nodulesmentioning
confidence: 99%
“…Описаны отдельные наблюдения множественных аспергиллезных узловых образований у пациентов с ревматоидным артритом [13,60], а также случаи сходства нодулярной формы ХАЛ с метастатическими инфильтратами [43].…”
Section: нодулярный аспергиллезunclassified